Structural controls of the migration of mantle-derived CO2 offshore in the Santos Basin (Southeastern Brazil) - Plawiak, Rafael André Belotto; Carvalho, Marcelo José; Sombra, Cristiano Leite; Brandão, Davy Raeder; Mepen, Michelle; Ferrari, André Luiz; Gambôa, Luiz Antônio Pierantoni (Frontiers in Earth Science, 2024)
We present a multi-scale conceptual model based on structural controls for migration of mantlederived CO2 offshore Santos Basin (Southeastern Brazil). We assembled the model from a regional 2D seismic reflection line integrated with potential gravimetric field data, and a local 3D seismic reflection volume integrated with well data (lithologies and in situ stress). (i) Geochemical isotope range of δ 13 CCO2 fall mostly within -7‰ and -5‰ and show relatively high values for 3 He/ 4 He represented by R/Ra rate up to 5.60 indicating CO2 mantle generation and degassing. (ii) Seismic interpretation feasibly validated by potential gravimetric responses -crustal structure (Moho discontinuity) show CO2 migration through deep-seated faults in a region of highly stretched continental crust with oceanward mantle uprising. (iii) Early Cretaceous basement highs generated in an obliquely syn-rift faulting system control CO2 accumulation in thermogenic travertines (hydrothermal carbonate reservoirs of continental lakes), and Aptian evaporites subsequently trap it. Comentado [RBP1]: We translated the Institutions' names and added current Institution of the first author Comentado [RBP2]: Added a Comentado [RBP3]: Added a Comentado [RBP4]: It is correct in the Word format Comentado [RBP5]: Added fall Comentado [RBP6]: Added show Comentado [RBP7]: It is correct in the Word format Comentado [RBP8]: Added indicating Comentado [RBP9]: Changed to singular Comentado [RBP10]: Excluded and Conrad Comentado [RBP11]: Changed to singular Comentado [RBP12]: Excluded Lower Comentado [RBP13]: Added Early Comentado [RBP14]: Excluded the Comentado [RBP15]: Corrected to activity Comentado [RBP20]: Added the Comentado [RBP21]: Added the Comentado [RBP22]: Corrected Km to km Comentado [RBP23]: Added the Comentado [RBP24]: Added that 10 References